FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Ria Adhotul Khasanah, 13.05.52.0243; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2017)
The study examines the effect of profitability, asset structure, growth of company, farm size, business risk, tax dan liquidity on capital structure. This research on manufacturing company on the Indonesian Stock Exchange by using a go public.Â The sampling method used purposive sampling with periode from 2013 to 2015. The data are processed as many 179 companies. The thechnique of data testing using multiple linear regression analysis. The results showed that the profitablility, asset structure, and liquidity has negative effect and significant to the capital structure, growth of company has positive effect and significant to the capital structure, farm size, business risk, and tax does not have any influence to the capital structure.Keywords: Profitability, Asset Structure, Growth of Company, Farm Size, Busines Risk, Tax dan Liquidity